Molecular Response to Extreme Summer Temperatures Differs Between Two Genetically Differentiated Populations of a Coral Reef Fish - Veilleux, Heather D.; Ryu, Taewoo; Donelson, Jennifer M.; Ravasi, Timothy; Munday, Philip L. (Frontiers in Marine Science, 2018)
Extreme thermal events are increasing in frequency and duration as the climate continues to warm, with potential detrimental effects on marine organisms. However, the effects of heatwaves may differ among geographically separated populations depending on their capacity for thermal plasticity. Here, we compared the response to simulated summer heatwave temperatures (+1.5 and +3.0 ˚C above average) in two populations of a coral reef damselfish with different capacities for thermal plasticity. We found that the more thermally tolerant population had greater plasticity of gene expression and had significantly more downregulated genes, which may provide more energy to repair damage associated with thermal stress and to maintain basic functions at these extreme temperatures. In contrast, the thermally sensitive population exhibited higher basal levels of heat shock proteins and had three times fewer changes in gene expression overall. The limited changes in gene regulation suggest that individuals have reduced genome plasticity to tolerate thermal fluctuations and consequently may not have enough energy to repair damage and resume cellular homeostasis at extreme temperatures. Thus, we have identified the molecular signatures of how two genetically distinct fish populations cope with an extreme thermal event, and why they differ in their capacity for thermal plasticity.